(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The advent of digitalization has significantly shaped the healthcare sector, introducing advanced technological solutions while simultaneously exposing health infrastructures to ever-evolving cyber threats. This paper aims to bridge the gap between key disciplines – medical science, IT, and law – realities that are often ideologically distant but must now collaborate to address the growing digital risks in healthcare. To this end, interviews have been conducted with two professionals embedded in the healthcare system – a telesurgeon and a computer engineer – whose insights will be presented. Through their perspectives, this paper seeks to “diagnose” the current and future challenges related to cybersecurity in healthcare.